2013
DOI: 10.2147/dddt.s42390
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of mammalian target of rapamycin (mTOR) enhances radiosensitivity in pancreatic carcinoma cells

Abstract: The mammalian target of rapamycin (mTOR) is a protein kinase that regulates protein translation, cell growth, and apoptosis. Rapamycin (RPM), a specific inhibitor of mTOR, exhibits potent and broad in vitro and in vivo antitumor activity against leukemia, breast cancer, and melanoma. Recent studies showing that RPM sensitizes cancers to chemotherapy and radiation therapy have attracted considerable attention. This study aimed to examine the radiosensitizing effect of RPM in vitro, as well as its mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…Rapamycin‐induced autophagy in MCF‐7 breast cancer cells delayed the attendance of Rad51 and breast cancer 1 (BRCA1) in DSBs upon radiotherapy, leading to the accumulation of DSBs and cell death . Similarly, the sensitivity of pancreatic carcinoma cell PC‐2 to radiotherapy was significantly enhanced post‐rapamycin treatments, and the upregulation of autophagy mediator Beclin‐1 sensitized lung cancer cells to irradiation , . These findings suggest that autophagy may play an important role in cancer radiotherapy.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Rapamycin‐induced autophagy in MCF‐7 breast cancer cells delayed the attendance of Rad51 and breast cancer 1 (BRCA1) in DSBs upon radiotherapy, leading to the accumulation of DSBs and cell death . Similarly, the sensitivity of pancreatic carcinoma cell PC‐2 to radiotherapy was significantly enhanced post‐rapamycin treatments, and the upregulation of autophagy mediator Beclin‐1 sensitized lung cancer cells to irradiation , . These findings suggest that autophagy may play an important role in cancer radiotherapy.…”
Section: Introductionmentioning
confidence: 89%
“…The experiment was performed as previously described . In brief, A549 cells were seeded into wells of a six‐well plate with a concentration of 200 cells per well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of the mTORC1 can activate the ULK1 complex and promote the interaction with the PtdIns3K complex which is necessary for the formation of new autophagosomes (47). Several studies have reported on the positive effects of mTOR inhibitor on sensitizing cancers to radiation therapy and chemotherapy in lung cancer, pancreatic carcinoma cells and esophageal carcinoma cells (48)(49)(50)(51).…”
Section: Dna Damage Repair and Autophagymentioning
confidence: 99%
“…These anti-cancer effects of EGCG on pancreatic cancer cells are mediated through the up-regulation of PTEN expression and the down-regulation of phospho-Akt and phospho-mTOR, suggesting the molecular regulation of EGCG on Akt/mTOR signaling. Importantly, the targeted inhibition of mTOR signaling has been found to enhance radiosensitivity in pancreatic carcinoma cells (109), suggesting that the suppression of mTOR signaling by nutraceuticals such as metformin and EGCG could potentiate the anti-cancer activity of radiation therapy for achieving better treatment outcomes in patients diagnosed with pancreatic cancer.…”
Section: Nutraceuticals For Pancreatic Cancer Treatmentmentioning
confidence: 99%